Effect of a Prosthetic Foot with a Hydraulic Ankle Unit on the Contralateral Foot Peak Plantar Pressures in Individuals with Unilateral Amputation. Issue 3 (July 2018) - Moore, Raymond
ABSTRACT: Introduction: Since their release, prosthetic feet with integrated hydraulic ankle units have proved a popular prescription choice among individuals with lower-limb amputation. This study evaluates the effect of including this type of prosthetic foot on the peak plantar pressures of the patient's contralateral foot. Case Description and Methods: Peak plantar pressures of 14 participants with established K3 activity levels were measured before and after the addition of a prosthetic foot with hydraulic ankle unit using the Amcube pressure plate. Results: The results showed a statistically significant reduction in contralateral peak plantar pressures with the use of a prosthetic foot containing a hydraulic ankle unit. Conclusions: The benefits of changing to a prescription including a foot with integrated hydraulic ankle unit can have significant effects on the forces acting on the remaining foot of an individual with amputation.